Recommendations for prevention and management of COVID-19 in peritoneal dialysis patients - Xue-Li Lai (KeAi Communications Co., Ltd., 2020)
The World Health Organization characterized coronavirus disease (COVID-19) as a pandemic on March 11, 2020. Peritoneal dialysis patients have a weakened immune system that is associated with a high morbidity of infection. Thus, COVID-19 prevention measures and management for patients on peritoneal dialysis are urgent and critical. Based on published research on COVID-19 and previous clinical practices for similar coronavirus outbreaks, we aimed to make recommendations to manage patients undergoing peritoneal dialysis.